Utilizing ATLS® Trauma Management Protocols: the gold standard for safe and effective care - Dogjani, Agron; Selmani, Edvin; Zaimi, Edmond; Haxhirexha, Kastriot; Biberaj, Petrit; Lenjani, Basri; Subashi, Kastriot; Hasmuca, Ilir; Zogaj, Erjona; Blloshmi, Amarildo; Doci, Klevis; Mulita, Francesk (Family Medicine & Primary Care Review, 2025)
Approximately 5.8 million people die each year because of trauma. Traumatic injury is the leading cause of death under the age of 45 in the U.S. and worldwide. Traumatic injuries represent a significant global health burden, often demanding swift and decisive intervention to mitigate morbidity and mortality. The Advanced Trauma Life Support (ATLS) course has become a cornerstone in trauma management, providing healthcare providers with a systematic approach to assessment, resuscitation, and definitive care. This article explores the pivotal role of ATLS protocols as the gold standard for safe and effective trauma management. ATLS protocols prioritize a structured assessment methodology, employing the ABCDE approach to identify and address life-threatening injuries rapidly. By adhering to this systematic framework, healthcare providers can promptly initiate time-critical interventions, minimizing the risk of adverse outcomes. Moreover, ATLS protocols promote standardization of care, ensuring consistent management practices across diverse clinical settings. Through multidisciplinary collaboration and continuous training, healthcare teams are equipped to deliver coordinated and efficient care, optimizing patient outcomes. In conclusion, ATLS trauma management protocols represent more than a guideline; they embody a commitment to excellence in patient care. By embracing the principles of ATLS, healthcare providers uphold the gold standard for safe, effective, and compassionate trauma management, ultimately saving lives and restoring hope in times of crisis.